Facilidades e dificuldades de alunos da Educação de Jovens e Adultos sobre o currículo de Matemática - Neves, Elizandra Pires (2020)
The main objective of this research was to identify, analyze and understand the facilities and learning difficulties of EJA students in relation to the Mathematics curriculum. And, as a specific objective: to analyze elements that may facilitate the process of teaching and learning Mathematics at EJA. The question guiding this study is: What are the facilities and learning difficulties of EJA students in relation to the Mathematics curriculum? We take Lev Semyonovich Vygotsky's thinking and Historical-Cultural Theory as our theoretical foundation and develop a qualitative approach research based on bibliographic documents, our reflections on observations about the reality of EJA's Mathematics classes and also on the reports of 9th Period EJA students from a municipal school in Uberlândia-MG. Among the main results of this work, we highlight the importance of the organization of the curricular time and the use of didactic materials during the teaching and learning process. According to students' reports, in relation to the learning of the contents proposed in the Mathematics curriculum, and to the observations made during classes by the researcher, these elements accompany the teacher's practice in the classroom and directly interfere in the teaching and learning process, since it is in time, organized by the school, that EJA students trust their expectations of learning and social ascension. The use of teaching materials serves as an incentive for the students' interest and as auxiliary tools for understanding and fixing the proposed curriculum content.